Profiling readiness for deep learning: A study of chemistry students' multiple intelligences and learning reflections - Iriani Bakti; Atiek Winarti; Ni Pt. Pande Mirah Surya Dewi; Mahdian; Syarifah Meutiah Eka Sari (Indonesian Journal of Educational Development (IJED), 2026)
The persistent challenge of promoting deep conceptual understanding over rote memorization in chemistry education requires investigating students' readiness for student-centered learning. This study aims to screen student readiness for deep learning in chemistry by analyzing their multiple intelligences (MI) and reflective learning experiences. Employing a qualitative descriptive method, this study analyzed data from an MI questionnaire and reflective writing assignments from 84 Chemistry Education students (2022–2024 cohorts) selected via purposive sampling at Universitas Lambung Mangkurat. Results revealed that spatial intelligence is the most dominant profile, with 23 of 84 students in this category. Analysis of reflective writing identified Project-Based Learning (PjBL) as the most preferred instructional model for creating meaningful learning experiences, with 29 respondents favoring it. Furthermore, student reflections demonstrated a significant transformation from negative assumptions to deeper understanding, highlighting the development of creativity, critical thinking, and teamwork. These findings suggest that leveraging visual and project-based strategies aligned with students' dominant intelligence and learning preferences can effectively foster readiness for a deep learning approach in chemistry education.